Clinical Features Predictive of Survival in Patients With Vitreoretinal Lymphoma: Analysis of 70 Patients at a Single Ocular Oncology Center. Issue 2 (March 2020) - Dalvin, Lauren A.; Lim, Li-Anne S.; Ancona-Lezama, David; Mazloumi, Mehdi; Chang, Michael; Porcu, Pierluigi; Martinez, Nina L.; Glass, Jon; Mashayekhi, Arman; Shields, Carol L.
Abstract : Purpose: The aim of this study was to identify clinical factors predictive of time to central nervous system (CNS) lymphoma or death in patients with vitreoretinal lymphoma (VRL). Design: Retrospective cohort study. Methods: Patients with VRL (n = 95 patients) from Januray 1, 1984 to July 30, 2018 were identified at a single ocular oncology center and records were retrospectively reviewed. Outcomes included Kaplan-Meier estimated time to CNS lymphoma and death. Results: There were 95 patients with VRL diagnosed at mean age 67 years, of which 70 patients had follow-up with the ocular oncology service. Mean time to CNS lymphoma in patients with isolated VRL was 56 months and did not differ by age, sex, bilateral ocular involvement, retinal infiltration, subretinal pigment epithelial (sub-RPE) infiltration, or treatment with prophylactic systemic chemotherapy ( P  > 0.05). Mean time to death was 66 months and did not differ when comparing those with CNS lymphoma diagnosed before VRL versus after VRL versus no CNS lymphoma at any time (67 vs 60 vs 64 months, P  > 0.05). Presence of sub-RPE infiltration was associated with shorter mean time to death (46 vs 76 months, P  = 0.04, odds ratio 1.9). Older patient age was associated with increased risk of death (odds ratio 1.0, P  = 0.02). The mean time to death did not differ by sex, bilateral ocular involvement, retinal infiltration, timing of CNS or systemic lymphoma, or treatment with prophylactic systemic chemotherapy ( P  > 0.05). Conclusions: Patients with VRL presenting with sub-RPE infiltration could have shorter mean survival time. Further studies are required to confirm these findings and determine whether sub-RPE infiltration is associated with more aggressive CNS lymphoma.